Plasma Brain Natriuretic Peptide Levels in Children with Chronic Kidney Disease and Renal Transplant Recipients: A Single Center Study - Anastasia Garoufi; Aikaterini Koumparelou; Varvara Askiti; Panagis Lykoudis; Andromachi Mitsioni; Styliani Drapanioti; Georgios Servos; Maria Papadaki; Dimitrios Gourgiotis; Antonios Marmarinos (MDPI AG, 2022)
Pediatric chronic kidney disease (CKD) patients, as well as kidney transplant patients, are at an increased risk of developing cardiovascular disease. BNP measurement, as a biomarker of cardiovascular risk, has been recommended to this high-risk population. Plasma BNP levels were measured in 56 CKD children in either pre-dialysis stage, hemodialysis (HD) or renal transplant recipients (RTRs) and in 76 sex- and age-matched healthy controls. BNP levels were investigated in HD children, before and after the completion of their HD session. BNP levels in total CKD population, in pre-dialysis stage patients and on HD were significantly higher, compared to the respective controls. HD children had higher BNP levels compared to CKD patients in the pre-dialysis stage. Moreover, post-HD BNP concentration was slightly higher than pre-HD, with the difference being marginally statistically significant. BNP was positively correlated with eGFR, creatinine, cystatin-C and parathormone and negatively with albumin and 25-hydroxyvitamin D. A positive correlation between BNP concentration and the ratio of E/A in pulse-wave Doppler echocardiography was also observed. In conclusion, CKD pediatric patients, mainly those undergoing HD, have high plasma BNP levels which do not decrease after the HD session. This is indicative of a greater risk for future cardiovascular disease.